HOW DO YOU FIND OUT IF THE PRICE YOU HAVE SET IS CORRECT? - Iv. Kostova (Trakia Journal of Sciences)
Business owners should look at it as a struggle of views. Customers strive to reduce everything to the simplest possible comparable level. Businesses, on the other hand, must strive to prevent this. If the prevention process is successful, the customer cannot make a reasonable comparison based on price alone. Create in the customer's mind the feeling that the business, product or service is different and success in the long run can be yours. Create in the client a sense of differences that have real value for him. The article has examples of perceived value and how it can be converted into better prices and greater profits. Before we can follow this topic, we need to know if pricing is an issue in your business. This article shows you several ways to find out if your prices are too low.